Montreal Museum of Fine Arts, collection of Mediterranean antiquities - Caron, Beaudoin. (Monumenta Graeca et Romana, 2008)
This catalogue raisonné describes a little-known but very interesting collection originally assembled by one of the important Canadian collectors of the early 20th century. After an account of the collection's history and a brief discussion of the techniques of ancient glass-making, the catalogue proper presents 191 pieces comprising a very wide range of typical forms, each of them fully illustrated. Publishing this extensive collection renders it available to a wide readership: students, curators, archaeologists, art historians, collectors and everybody with serious interest in the material culture of the ancient world. It is the first of a series intended to make public the different parts of the museum's collection of Mediterranean antiquities.